CAN CHANGES IN THE SETD5 AND SHANK3 GENES BE ASSOCIATED WITH A WORSE PROGNOSIS OF AUTISM? - Lavínia Mota de Miranda, Eduarda; Karoline Lacerda Sousa Silva, Ana; Paula Vasconcelos Páuda, Ana; Emanuele Pereira Domingues, Fernanda; Orlandi Rosa, Letícia; Marques Araújo, Francielle; Thalita dos Reis, Sabrina (Health and Society, 2022)
Autism spectrum disorder (ASD) is a genetic neuropsychomotor disorder and environmental. In recent years, much has been discussed about the risk factors associated with ASD development. In this sense, environmental, genetic and epigenetic factors have been highlighted. Mutations in the SETD5 and SHANK3 genes were associated with TEA phenotypes, considering different signs and symptoms. The SETD5 gene is related to cognitive changes such as intellectual disability, speech/developmental delay. On the other hand, children with mutations in the SHANK3 gene express indicators associated with a more aggressive and epileptic conditions. The SETD5 and SHANK3 genes are intrinsically related to the ASD phenotype, however such genetic alterations associated with ASD are not well understood, therefore, research and studies on the subject should be carried out. this review compiles the results of the analysis of changes in such genes and assesses which of them represent a worse prognosis for a patient diagnosed with autism, in order to promote an early diagnosis, better quality of life and, perhaps, in the future, a more directed.